Analisis Pengukuran Tingkat Kesehatan Bank Menggunakan Metode Camels dan RGEC pada Bank Konvesional yang Terdaftar di BEI Periode Tahun 2019-2023 - Aurellia Bunga Wana Citra (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
A bank is an institution that collects public funds in the form of savings. This study aims to analyze the health levels of banks listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023 using the Camels and Rgec methods. This research utilized a quantitative descriptive approach. The research population consisted of state-owned banks listed on the BEI, with a sample size of 4 companies: BNI, BRI, BTN, and Mandiri. Data collection techniques involved documentary methods using secondary data, specifically the financial reports of state-owned banks available on the BEI or respective bank websites. The research findings indicate that for Bank BNI, the Camels score indicates a healthy status with a score of (90.84), while the Rgec score indicates a very healthy status with a score of (90.66). For Bank BRI, the Camels score suggests a fairly healthy status with a score of (71.65), and the Rgec score indicates a very healthy status with a score of (86.67). Bank BTN shows a less healthy status with a Camels score of (60.89), but a healthy status with an Rgec score of (76.67). Bank Mandiri exhibits a less healthy status with a Camels score of (62.02), while the Rgec score indicates a very healthy status with a score of (87.33).